Design and Evaluation of Nanoparticle Formulations for Improved Drug Bioavailability - Shahnawaz, Mohd; Sharma, Shalini; Ain, Shabnam; Ain, Qurratul (Journal of Neonatal Surgery, 2025)
Bioavailability is an important component in the effectiveness of oral medication formulations because it determines the amount and pace at which a drug reaches its target site of action. Poor solubility and absorption are significant hurdles to the development of many promising medication candidates. Nanotechnology, namely nanoparticle-based medicine delivery systems, has emerged as a viable answer to these issues. This study investigates the use of nanotechnology to improve drug solubility, stability, and bioavailability via several nanoparticle formulations, including lipid nanoparticles, magnetic nanoparticles, and polymeric nanoparticles. These nanocarriers not only improve drug solubility, but also provide controlled and prolonged drug release, preserve pharmaceuticals from degradation, and allow for targeted distribution to specific areas in the body, thereby reducing adverse effects. Furthermore, the integration of artificial intelligence (AI) and computational tools has improved nanoparticle design, allowing for the development of tailored therapeutics. The paper focuses on major advances in nanotechnology and its role in altering drug delivery systems, with promising methods for increasing the bioavailability of poorly soluble medicines. Despite advancements, difficulties like as scalability, regulatory constraints, and long-term biocompatibility must be addressed to ensure successful clinical translation